PENINGKATAN KUALITAS PEMUKIMAN KUMUH DI KABUPATEN LEBAK TAHUN 2024 - Sumatirta, Edi; Putri, Widya; Raihan, Raihan (Jurnal Abdimas Bina Bangsa, 2025)
The mandate of Law No. 1 of 2011 concerning Housing and Residential Areas states that the State is responsible for protecting all Indonesian people through the provision of housing and residential areas so that people are able to live and occupy decent and affordable homes in healthy, safe, harmonious and sustainable housing throughout Indonesia. Furthermore, the law also states that the definition of a house is one of the basic human needs that has a strategic function as a habitable place to live, a means of family development, a reflection of the dignity of its occupants, and an asset for its owner. To implement this policy, the regional government through the Public Housing and Residential Area and Land Service of Lebak Regency, provides assistance to improve the quality of uninhabitable houses for Low-Income Communities in Lebak Regency through Self-Help Housing Stimulus Assistance (BSRS) in the Arrangement and Improvement of the Quality of Slum Areas with an area of ​​less than 10 Ha sourced from the 2024 Regional Budget and Revenue and Expenditure with a program target of 300 housing units